Student-faculty partnership in design: Evaluating a co-creation practice and sharing of findings within the South African higher education context - Botha, A.J.M.; Steyn, A.A. (South African Journal of Higher Education, 2020)
Creation of content in the higher education context has long been considered as a faculty responsibility. However, a drive towards inclusive curriculum transformation was requested by both students and professional accreditation bodies. Teamwork, as part of partnerships and co-creation, is seen as a critical skill for socio-economic development throughout the world, with the industry expecting competent team players. Faculty has long been incorporating teamwork into modules; however, teaching teamwork and tracking these skills remain challenging. Thus, leaving a gap where students form groups and work in teams without the cognisance to improve their teamwork skills or increase the reliability and validity of evaluating team members’ participation and contributions. In the absence of a comprehensive institutional resource on teamwork fundamentals, this study explores the co-creation of such a resource by post-graduate students at a higher education institution in South Africa. As higher education institutions, we assess students on teamwork skills, but we never specifically teach this to students, this resource is addressing this specific need. This will enable higher education institutions to report on assurance of learning where students can demonstrate the competency to effectively work in teams. A project approach was followed in the design of the teamwork resource based on Mayer’s Principles for designing multimedia for e-learning. Tuckman’s five stage development process informed the content design. The project ran over three weeks with weekly scrum meetings monitored by faculty. The study found that co-creating content with students is possible. However, student partnerships can enable quality improvement of teaching and assessing teamwork skills. Finally, the researchers will outline how the practical strategies for enacting partnership, as suggested in the literature, were considered in their practice.